An Implementation of an Internal Quality Assurance System in Improving the Quality of Senior High School Education: A Systematic Literature Review - Mukhlisin, Muhammad Khoirul; Ulfatin, Nurul; Muyassaroh, Muyassaroh (Universitas Al-Qolam Malang, 2024)
Internal quality assurance is implemented by referring to national education standards, to realize national education goals. Internal quality is now not only applied in universities, but is also applied in primary and secondary education. So that quality assurance and fulfillment of education quality standards in primary and secondary education units are more guaranteed and focused. This article is the result of analysis by reviewing literature related to the topic of discussion. The aim of this research is to determine and describe the implementation of the Internal Quality Assurance System cycle. The model used is literature study or literature review. The results of this research show that quality improvement activities implemented in accordance with the stages of the SPMI cycle carried out by senior secondary schools include: one, school self-evaluation based on education quality report cards, second, quality improvement planning by establishing a quality assurance committee and re-analyzing the evaluation results. school itself, third, implementation of quality improvements, fourth, monitoring, evaluation and results of quality improvements after quality improvements have been carried out, and fifth, quality planning again for the coming year. The results of implementing internal quality assurance have an impact on a more innovative learning process, student achievement and school achievement, to customer satisfaction both internal and external, as well as fulfillment of eight national education standards. Keywords: Implementation, Quality Assurance, Internal Quality